2015
DOI: 10.1007/s12034-015-0902-3
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of pure cordierite and zirconia-doped cordierite ceramic composite by precipitation technique

Abstract: Pure cordierite and cordierite-ZrO 2 composite (5-20 wt%) ceramics for various stoichiometric compositions were synthesized from standard raw materials by a novel precipitation technique. The analytical techniques such as X-ray diffraction, simultaneous thermogravimetric and differential thermal analysis, Fourier transform infrared spectroscopy, scanning electron microscopy and bulk density were employed to evaluate the properties and microstructure. Results show that the ceramic composites consist of cordieri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The patterns at 600 and 800 0 C indicate the amorphous nature and above this temperature, formation of µ-cordierite (metastable) and cristobalite up to 1200°C. The solid state reaction synthesis at 1400°C for 3 h indicated the presence of stable α-cordierite, which is evident from the previous research the αcordierite formation occurs within 1h to 12 h [17]. XRD patterns for various zirconia compositions (5-15 wt%) are shown in figures 1and 2 for various sintering temperatures.…”
Section: Resultssupporting
confidence: 67%
“…The patterns at 600 and 800 0 C indicate the amorphous nature and above this temperature, formation of µ-cordierite (metastable) and cristobalite up to 1200°C. The solid state reaction synthesis at 1400°C for 3 h indicated the presence of stable α-cordierite, which is evident from the previous research the αcordierite formation occurs within 1h to 12 h [17]. XRD patterns for various zirconia compositions (5-15 wt%) are shown in figures 1and 2 for various sintering temperatures.…”
Section: Resultssupporting
confidence: 67%
“…Aluminosilicate-based cordierite has attracted attention as a ceramic that can offer a combination of properties varying from excellent thermal shock resistance resulting from its low thermal expansion coefficient, high thermal and chemical stability, high refractoriness, and mechanical strength. [1][2][3][4][5] The aluminosilicate-based cordierite having 2MgO.2Al 2 O 3 .5SiO 2 composition can be produced as dense ceramic, porous ceramic, glass, or glass-ceramic by methods such as solid-state sintering (SSS), liquid phase sintering (LPS), and melting. Due to the range of properties it offers, cordierite is widely used in industrial applications such as diesel particulate filters, 6 the filter element of advanced power generation systems, 7,8 insulators for continuous flow electric water heaters and other heating systems, spark protectors, and catalyst carriers in automobiles, 9 heat exchangers for gas turbines 10 substrates of catalysts for exhaust gas emissions control in automobiles.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In several studies, it has been reported that the addition of fine ZrO 2 to cordierite affects the sinterability and improves mechanical properties. 1,3,5 However, the effect of ZrO 2 added to cordierite on corrosion resistance has not been sufficiently investigated. Therefore, this work aims to investigate the corrosion behavior of ZrO 2 doped cordierite obtained from natural zeolite by evaluating their corrosion kinetics in dilute HCl solution of different concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for synthesizing nanocrystalline α-cordierites such as solid state reaction [5], sol-gel [6], spray pyrolysis [7], co-precipitation method [8], and combustion synthesis method with flame or without flame [9]. The Pechini method is similar to solgel technique with some advantages such as being economic and affordable, utility, control of stoichiometry, low processing temperature, and high degree of homogeneity.…”
Section: Introductionmentioning
confidence: 99%